Peningkatan Disiplin pada Siswa Berkebutuhan Khusus Melalui Pembelajaran Pendidikan Kewarganegaraan di SLB-B Kota Bandung - Reza Wahyuni; Anwar Rahman (Departement of Mathematics Education, 2024)
Citizenship education has a very significant role in the process of instilling disciplined character in deaf students. Considering that there are incidents of disciplinary violations that often occur in schools, especially in schools with special needs, it is important to apply disciplinary character to students with special needs at SLB-B Cicendo, Bandung City. The method used in this research is qualitative with descriptive methods. An important finding is that Citizenship Education subjects have succeeded in becoming an appropriate means of instilling character education in students in terms of time discipline, rules of conduct, attitudes towards the learning process and worship. The conclusion of this research is that deaf students can overcome limitations in achieving maximum learning outcomes assisted by special education teachers in carrying out the knowledge transfer process well.